Preparation and modifying a new type of waxes - Nadira A Hatim; Amer A Taqa; Wafa M Abbas (University of Mosul, College of Dentistry, 2006)
Abstract that has almost the same properties of dental modeling wax used in dentistry. Materials and Methods: Three groups of waxes (220 samples) with different compositions regarding its origin (Al-Dora refinery waxes, natural bees wax-North of Iraq, and commercially available Iraqi waxes), additives such as starch, sodium-carboxyl methylcellulose (Na-CMC), rosin, or nylon, and coloring agents were prepared. The samples were tested for their melting range, 21 samples only had a melting range that nearly coincides with that of the dental waxes such as Major and Cavex. Results: The resultant 21 samples were tested for their softening, trimming, penetration, residue materials and solubility. Only 4 samples showed properties that are closely similar to that of Major and Cavex wax. The results of melting point ranged from 69-80oC. Softening test showed that the samples which contain nylon, Na- CMC, or rosin were softened without adhering to the fingers. Trimming test showed that they were trimmed easily and clearly. Penetration test showed that, some samples had the similar measurements of Major and Cavex wax (0.6-0.9mm). Residue materials showed that all samples had no residue of wax materials on acrylic teeth after wax elimination procedure. All the prepared waxes were soluble in ether (acetone), and petroleum spirit (benzene). Conclusion: Six new modeling wax materials were prepared according to ADA specification No.24. Three of new wax materials consist of nylon(polystyrene 1.71-2.13%); the other two novel modeling waxes were fabricated by using additive materials (Na-CMC and rosin).